Rooftop PV with battery storage for constant output power production considering load characteristics - Jabalameli, Nasim; Deilami, Sara; Masoum, Mohammad Sherkat; Shahnia, Farhad (IEEE, 2013)
One of the main limitations of rooftop photovoltaic generation systems (rooftop PVs) is the dependency of their output power to environmental factors such as sun radiation, panel temperature, passing clouds and shading, as well as loading level (operating point on v-i characteristics). This dependency may result in sudden output power variations of rooftop PVs particularly during cloudy periods. This paper investigates application and control of battery storage (BS) systems to overcome the sudden output power variations of rooftop PVs. A practical battery storage energy management strategy (BS-EMS) for operating grid-connected rooftop PVs at point of common coupling (PCC) is presented such that the delivered output power to the grid is constant under various operating conditions. The power balance between rooftop PV, BS and grid is considered by dynamic control of the BS converter to achieve constant output power to the grid during daylight. Simulation results for a 24-hour period will be presented and analyzed to investigate the performance of BS-EMS for a system comprising of a single-phase rooftop PV with BS and linear loads connected to power grid.